Workpiece-scale numerical simulations of SLM molten pool dynamic behavior of 316L stainless steel. (15th August 2021) - Cao, Liu
Abstract: 316L stainless steel is currently one of the most critical stainless-steel materials due to its excellent corrosion resistance and comprehensive mechanical properties. Selective laser melting (SLM), as an additive manufacturing technology for directly forming complex metal parts, has been applied in the production of 316L stainless steel components. By introducing reasonable and comprehensive equivalent processing models (e.g., gasification pressure, gasification heat dissipation, and equivalent physical parameters), a predictive model of the dynamic behavior of the molten pool on the workpiece scale (two-phase flow model) was established for the SLM process of 316L stainless steel. The related equivalent processing models were customized by secondary development means based on the commercial software Fluent. By comparing and analyzing the different calculation schemes, it was found that surface tension stabilizes the liquid metal surface, while the Marangoni effect and the gasification recoil force cause the liquid metal surface to appear concave. The tangential movement of the liquid metal surface, caused by the Marangoni effect, causes the molten metal to accumulate around the central region, forming a liquid surface morphology resembling a crater. The influence of different processing parameters (scanning speed and laser power) on the SLM process of 316L stainless steel was analyzed. The simulated and experimentally obtained solidified track sizes were in good agreement.